A New Numerical Approach for Solving 1D Fractional Diffusion-Wave Equation. (6th January 2021) - Ali, Umair; Khan, Muhammad Asim; Khater, Mostafa M. A.; Mousa, A. A.; Attia, Raghda A. M.
Abstract : Fractional derivative is nonlocal, which is more suitable to simulate physical phenomena and provides more accurate models of physical systems such as earthquake vibration and polymers. The present study suggested a new numerical approach for the fractional diffusion-wave equation (FDWE). The fractional-order derivative is in the Riemann-Liouville (R-L) sense. Discussed the theoretical analysis of stability, consistency, and convergence. The numerical examples demonstrate that the method is more workable and excellently holds the theoretical analysis, showing the scheme's feasibility.